Allogeneic Hematopoietic Stem Cell Transplantation in a Rare Case of Tonsillar Mast Cell Sarcoma - Kubasch, Anne Sophie; Franke, Georg-Nikolaus; Aldaoud, Ali; Weibl, Konstantin; Jentzsch, Madlen; Sabri, Osama; Horny, Hans-Peter; Fend, Falko; Behre, Gerhard; Platzbecker, Uwe; Vucinic, Vladan (Frontiers in Oncology, 2020)
Mast cell sarcoma comprises a rare aggressive mast cell neoplasia with histological, clinical and genetic features distinct from other mast cell neoplasm. Until now, prognosis is still poor due to high rates of progression to mast cell leukemia and failure of conventional chemotherapies. Our here presented first report about successful allogeneic hematopoietic stem cell transplantation leading to remission in a case of tonsillar MCS represents a promising potential curative treatment option for this rare and often fatal disease.